LITERATURE REVIEW: PROMOTIONAL SIGNAGE DAN IMPLIKASINYA TERHADAP PERILAKU KONSUMEN DI INDUSTRI RITEL FESYEN: LITERATURE REVIEW: PROMOTIONAL SIGNAGE AND ITS IMPLICATIONS FOR CONSUMER BEHAVIOR IN THE FASHION RETAIL INDUSTRY - Saifurohman; Gregorius Prasetyo Adhitama (Universitas Trisakti, 2025)
Literature Review: Promotional Signage and Its Implications for Consumer Behavior in The Fashion Retail Industry. The fashion retail industry in Indonesia has experienced significant growth in 2024, driven by economic recovery post-pandemic. This competitive landscape demands innovation, particularly in marketing strategies, to attract consumers and enhance their in-store shopping experience. One such strategy is promotional signage, a visual marketing tool designed to capture attention, provide information, and influence purchasing decisions. This study aims to explore the impact of promotional signage on consumer behavior in fashion retail stores. Utilizing a literature review method, this research systematically analyzes previous studies on the role of promotional signage in guiding consumer movement, increasing product visibility, and shaping shopping experiences. Findings indicate that effective signage can significantly influence consumer attention, navigation, and purchase behavior. Well-designed promotional signage not only enhances the aesthetic appeal of retail spaces but also acts as a navigational guide that directs consumers toward specific areas of interest. Additionally, signage plays a crucial role in impulse buying and brand communication. The study concludes that promotional signage is a strategic component of visual merchandising, contributing to consumer engagement, purchase decisions, and overall shopping satisfaction. Retailers should focus on designing promotional signage that is visually appealing, strategically placed, and aligned with brand identity to optimize consumer experience and increase sales conversion.